Nasotracheal vs. Orotracheal Intubation and Post-extubation Airway Obstruction in Critically Ill Children: An Open-Label Randomized Controlled Trial - Kumar, Vijay; Angurana, Suresh Kumar; Baranwal, Arun Kumar; Nallasamy, Karthi (Frontiers in Pediatrics, 2021)
Background: The data on long-term nasotracheal intubation among mechanically ventilated critically ill children is limited. The purpose of this study was to compare the rate of post-extubation airway obstruction (PEAO) with nasotracheal and orotracheal intubation. Methods: This open-label randomized controlled trial was conducted in the PICU of tertiary care and teaching hospital in North India from January-December 2020 involving intubated children aged 3 months-12 years. After written informed consent, children were randomized into nasotracheal and orotracheal intubation groups. Post-extubation, modified Westley’s croup score (mWCS) was used at 10-timepoints (0-minute, 30 minute, 1, 2, 3, 6, 12, 24, 36, and 48-hours after extubation) to monitor for PEAO. The primary outcome was the rate of PEAO, and secondary outcomes were time taken for intubation, the number of intubation attempts, complications during intubation, unplanned extubation, repeated intubations, tube malposition/displacement, endotracheal tube blockage, ventilator-associated pneumonia, skin trauma, extubation failure/re-intubation, duration of PICU stay, and mortality. Results: Seventy children were randomized into nasotracheal (n=30) and orotracheal (n=40) groups. Both the groups were similar in baseline characteristics. The rate of PEAO was similar between nasotracheal and orotracheal groups (10% vs. 20%, p=0.14). The maximum mWCS and mWCS at 10-timepoints were similar in the two groups. The time taken for intubation was significantly longer (85 seconds vs. 48 seconds, p<0.001) in the nasotracheal group, whereas other secondary outcomes were similar in the two groups. Conclusion: The rate of PEAO was not different between nasotracheal and orotracheal groups.